Electrochemical determination of lead in human blood serum and urine by anodic stripping voltammetry using glassy carbon electrodes covered with Ag–Hg and Ag–Bi bimetallic nanoparticles. Issue 34 (20th July 2018) - Valera, Danny; Sánchez, Mireya; Domínguez, José R.; Alvarado, José; Espinoza-Montero, Patricio J.; Carrera, Patricio; Bonilla, Pablo; Manciati, Carla; González, Gema; Fernández, Lenys
Abstract : The evaluation and application of glassy carbon electrodes modified with bimetallic nanoparticle deposits. Abstract : The evaluation and application of glassy carbon electrodes modified with bimetallic nanoparticle deposits of Ag–Hg and Ag–Bi for determination of Pb(ii ) is described. Deposition of the nanostructured bimetallic combinations on top of the glassy carbon (GC) substrate, previously covered with a Nafion (Nf) film, resulted in electrodes with substantially enlarged hydrogen evolution over-voltage. As indicated by scanning electron microscopy and atomic force microscopy images, most of the deposited nanoparticles, with an average size of 150 nm, were uniformly dispersed inside the Nafion net while a smaller amount remained on top of the embedded ones. Sensitivity tests of the AgBiNpNf/GC modified electrode produced a detection limit (DL), based on the 3s criterion, of 0.66 μg L −1 and 0.24 μg L −1 for the AgHgNpNf/GC electrode. Accuracy was assessed by comparison with quantification of Pb(ii ) in human blood serum and urine samples analyzed by atomic absorption spectrometry, using a continuous source high resolution atomic absorption spectrometer.